Prototipe Deteksi Letak Kebocoran Pipa dengan Optimalisasi Kinerja Penerimaan Paket LoRa menggunakan Pengkodean Parameter Fisik - Herdiyanto, Dedy Wahyu; Alfian, Freska Meliniar; Sarwono, Catur Suko; Setiabudi, Dodi; Eska, Andrita Ceriana; Laagu, Muh. Asnoer (Journal of Applied Computer Science and Technology, 2024)
The purpose of this research is to determine the effect of the physical coding of LoRa communications on monitoring water pipelines. Optimizing the performance of packet receivers in the LoRa communication system using coding on the physical parameters SF (spreading factor), BW (bandwidth), and CR (coding rate). The detection system consists of 3 sensor nodes, 3 intermediate nodes, and 1 receiver node. Data from these sensors is sent to a cloud database. The SX1278 LoRa communication module works using a 433 MHz frequency. During the transmission process on the LoRa communication system, optimization is carried out for receiving data packets using the parameter coding method of physical spread factors, bandwidth, and coding rate. As a result of the research, it is shown that the greater the value of the third parameter (SF, BW, and CR), such as improvement in packet reception performance, improvement in bit security, and increasing packet resistance to various disturbances in transmission, but the time required for sending data be longer. The optimal parameters for detecting pipe leak locations include SF 10, BW 500 KHz, and CR 4/8. The LoRa SX1278 scenario is optimal with a distance of 400 meters, where packet and byte reception are obtained 100%.